2006
DOI: 10.1074/jbc.m602627200
|View full text |Cite
|
Sign up to set email alerts
|

Indirubin Enhances Tumor Necrosis Factor-induced Apoptosis through Modulation of Nuclear Factor-κB Signaling Pathway

Abstract: Although indirubin is known to exhibit anti-cancer and antiinflammatory activities, very little is known about its mechanism of action. In this study, we investigated whether indirubin mediates its effects through interference with the NF-B path-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 69 publications
2
66
0
1
Order By: Relevance
“…Consistent with several previous reports that indirubin-3 0 -monoxime inhibits intracellular targets other than FGFR1 (Hoessel et al, 1999;Adachi et al, 2001;Leclerc et al, 2001;Xie et al, 2004;Sethi et al, 2006), we found that in NIH/3T3 cells indirubin-3 0 -monoxime inhibited the phosphorylation of CDK2 and Rb, a CDK-regulated protein involved in regulation of cellcycle progression. However, the concentration of indirubin-3 0 -monoxime required to inhibit Rb and CDK2 phosphorylation was higher for FCS-stimulated cells than for FGF-1-stimulated cells, that is, 20 and 5 mM, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with several previous reports that indirubin-3 0 -monoxime inhibits intracellular targets other than FGFR1 (Hoessel et al, 1999;Adachi et al, 2001;Leclerc et al, 2001;Xie et al, 2004;Sethi et al, 2006), we found that in NIH/3T3 cells indirubin-3 0 -monoxime inhibited the phosphorylation of CDK2 and Rb, a CDK-regulated protein involved in regulation of cellcycle progression. However, the concentration of indirubin-3 0 -monoxime required to inhibit Rb and CDK2 phosphorylation was higher for FCS-stimulated cells than for FGF-1-stimulated cells, that is, 20 and 5 mM, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, it was recently reported that indirubin derivatives were able to block Stat3 signaling by inhibiting the Src kinase activity and in this way induce apoptosis in human cancer cells (Nam et al, 2005), and also, bind to and inhibit glycogen synthetase kinase-3 (Leclerc et al, 2001;Polychronopoulos et al, 2004), aryl hydrocarbon receptor (Adachi et al, 2001), muscle glycogen phosphorylase b (Kosmopoulou et al, 2004) and c-Jun NH2-terminal kinase (JNK) (Xie et al, 2004). More recently, indirubin-3 0 -monoxime was found to inhibit the activation of nuclear factor-kB resulting in enhancement of apoptosis induced by tumor necrosis factors in human leukemic cells (Sethi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Cytotoxicity was assayed by the modified tetrazolium salt 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, as described previously (72).…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…Cytotoxicity Assay Cytotoxicity was assayed by the modified tetrazolium salt 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay as described elsewhere (20).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the effect of pinitol on TNF-dependent InBa phosphorylation and degradation, cytoplasmic extracts were prepared as described elsewhere (20) from cells that had been pretreated with pinitol and then exposed to TNF for various times. Cytoplasmic protein (30 Ag) was resolved by 10% SDS-PAGE, transferred to a nitrocellulose membrane, blocked with 5% nonfat milk, and probed with specific antibodies against InBa and phosphorylated InBa.…”
Section: Western Blot Analysismentioning
confidence: 99%